ANALISIS HUBUNGAN SIMULTAN KEBIJAKAN INVESTASI, HUTANG & DIVIDEN PERUSAHAN (Studi Kasus Perusahaan Property & Real Estate yang Terdaftar di BEI Tahun 2011-2014) - Efendi, Mochamad Yusuf; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this research is to analyze simultaneous relationship between the Investment Policy, Debt and Dividend of firms. The effect of Uncertainty and Sales Growth to Investment Policy, The effect of Asset Tangibility and Deficit Financing the Debt Policy and The effect of the Return On Asset (ROA) and Retained Earnings (RE) to the Dividend Policy of Property and Real Estate Firm listed on Indonesia Stock Exchange.Sample in this research were selected by using purposive sampling method with some criteria. The samples are 39 firm listed in Indonesia Stock Exchange 2011-2014 period. The statistic method that used in this research are descriptive analysis, classical assumption test (Normality test, Heteroscedasticity test, multicollinearity test, autocorrelarity test), simultaneous equation models analysis (Three Stage Least Squares), Hausman Test, hypothesis test (F-statistics Test, t-statistics test, and Coefficient of Determination Test).The results showed that The Investment Policy and Debt Policy have a negative and unrelated simultaneously, Investment Policy and Dividend Policy have a negative and unrelated simultaneously, Debt Policy and Dividend Policy have a negative and related simultaneously. Uncertainties have a negative and not significant to Investment Policy and Sales Growth have a positive and not significant to Investment Policy, Asset Tangibility have a positive and not significant to Debt Policy and Deficit Financing have a negative and significant to Debt Policy, Return on Assets (ROA) have a positive and significant to Dividend Policy and Retained Earnings (RE) have a positive and no significant to Dividend Policy.